Family Inheritance: Classical Antiquities Reused and Displayed in Byzantine Cities - Bevilacqua, Livia (Actual Problems of Theory and History of Art, 2015)
A small group of gates of Byzantine city walls were decorated with reused, ancient figural sculpture, including the figure of Heracles. In some cases, such as the herms arranged horizontally on the main gate to the citadel of Ankara, this subject had not been identified before. Along with providing a detailed analysis of the decoration of the Zindan Kapı at Ankara, this paper traces the occurrence of the same iconographical subject, in similar architectural and urban contexts. Other examples considered as a comparison are the “Gates of Heracles” in Ephesos, the “Golden Gate” in Constantinople and the arch in the Theodosian Forum in the same capital city.